Treatment with anti-RANKL antibody reduces infarct size and attenuates dysfunction impacting on neutrophil-mediated injury. (May 2016) - Carbone, Federico; Crowe, Lindsey A.; Roth, Aline; Burger, Fabienne; Lenglet, Sébastien; Braunersreuther, Vincent; Brandt, Karim J.; Quercioli, Alessandra; Mach, François; Vallée, Jean-Paul; Montecucco, Fabrizio
Abstract: Selective pharmacological treatments targeting reperfusion injury produced modest protective effects and might be associated with immunosuppression. In order to identify novel and better-tolerated approaches, we focused on the neutralization of receptor activator of nuclear factor kappa-B ligand [RANKL], a cytokine recently shown to activate inflammatory cells (i.e. neutrophils) orchestrating post-infarction injury and repair. Myocardial ischemia (60 min) and reperfusion injury was surgically induced in C57Bl/6 mice. In hearts and serum, RANKL was early upregulated during reperfusion. A "one-shot" injection with neutralizing anti-RANKL IgG during ischemia ameliorated myocardial infarct size and function, but not adverse remodeling (determined by Magnetic Resonance Imaging [MRI]) as compared to Vehicle or control IgG. These beneficial effects were accompanied in vivo by reduction in cardiac neutrophil infiltration, reactive oxygen species (ROS) and MMP-9 release. Anti-RANKL IgG treatment suppressed sudden peak of neutrophil granule products in mouse serum early after reperfusion onset. In vitro, RANK mRNA expression was detected in isolated mouse neutrophils. Co-incubation with neutralizing anti-RANKL IgG abrogated RANKL-induced mouse neutrophil degranulation and migration, suggesting a critical role of RANKL in neutrophil-mediated injury. Conversely, anti-RANKL IgG did not affect salvage pathways in cardiac cells (i.e. ERK p42/p44, Akt and STAT-3) or macrophage cardiac infiltration. Finally, treatment with anti-RANKL IgG showed no effect on B and T lymphocyte polarization (in serum, spleen and infarcted myocardium) and circulating chemokines as compared with Vehicle or control IgG. In conclusion, acute treatment with anti-RANKL IgG improved cardiac infarct size and function by potentially impacting on neutrophil-mediated injury and repair. Graphical abstract: Highlights: RANKL inhibition before reperfusion improves infarct size in mice. RANKL inhibition before reperfusion improves cardiac function in mice. RANKL-induced injury is associated with neutrophil degranulation and migration.